Implementing inflation targeting regimes: The case of Poland - Jan Gottschalk; David Moore (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1999)
This paper assesses the prospects for the new Polish monetary policy strategy of inflation targeting. Regarding the general requirements for implementing an inflation targeting strategy it appears that Poland has made sufficient progress in reducing fiscal dominance and hardening budget constraints. The paper also finds that the exchange rate has played a dominant role as a policy instrument, with the linkages between the short-term interest rate and inflation remaining unclear. Given this uncertainty, modification of some details of the strategy - such as widening the target range or lengthening the target horizon - might be helpful.
Keywords: E52; E58; 330; inflation targeting; transmission mechanism in Poland; Inflation Targeting; Geldpolitik; Transmissionsmechanismus; Übergangswirtschaft; Wirkungsanalyse; Schätzung; Polen